KELAYAKAN BUKU SAKU SEBAGAI MEDIA PEMBELAJARAN PADA SUB MATERI MANFAAT KEANEKARAGAMAN HAYATI KELAS X - Muftia, Dika; Syamswisna, Syamswisna; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to find out the feasibility of a pocket book as a sub-media for learning the benefits of biodiversity in 10th grade. This research was arranged with descriptive method and quantitative approach. The feasibility of pocket book was tested by two lecturers of Biology Education Study Programme FKIP Untan and three senior high school biology teachers in Ngabang, Landak regency. The results of the ethnobotany research were then implemented in the form of biodiversity pocket book learning media. Based on the evaluation of validators from SMAN 1 Ngabang, Pelita Ngabang High School and MAN 1 Ngabang obtained an average value of total validation of 3.81. This research was attempted to prove that the pocket book was valid and suitable to be used as a learning media in the sub-material for biodiversity benefits in 10th grade.Â Keywords: Biodiversity, Media, Pocket Book, Ngabang